2021
DOI: 10.1007/s41062-021-00717-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the properties of roller-compacted rubberized concrete modified with nanosilica using response surface methodology

Abstract: Globally there is continuous rapid production of waste tires due to an increase in vehicle usage, which is becoming a serious environmental issue as its disposal and reuse affect sustainability negatively. With concrete being the most commonly available man-made construction material, there is a serious concern over the sustainability of natural resources mostly aggregate. One of the ways to address problems related to waste tire disposal and sustainability of natural material is by incorporating the waste tir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The past studies revealed that the two-parameter Weibull distribution appeared to be more fitting and established distribution functions for determining concrete's dynamic and fatigue properties [56,57]. Similarly, a strong technique namely response surface methodology have been used to evaluate the concrete performance [58][59][60], such as statistical analysis, prediction, and optimization. Therefore, the Weibull distribution function demonstrates an ascending or descending hazard function that reflects the actual concrete structure's performance [61].…”
Section: Impact Resistance Analysis Using Weibull Distributionmentioning
confidence: 99%
“…The past studies revealed that the two-parameter Weibull distribution appeared to be more fitting and established distribution functions for determining concrete's dynamic and fatigue properties [56,57]. Similarly, a strong technique namely response surface methodology have been used to evaluate the concrete performance [58][59][60], such as statistical analysis, prediction, and optimization. Therefore, the Weibull distribution function demonstrates an ascending or descending hazard function that reflects the actual concrete structure's performance [61].…”
Section: Impact Resistance Analysis Using Weibull Distributionmentioning
confidence: 99%
“…For the trending concrete types such as SCC and RCC, the crumb rubber has revealed different guides on whether to replace coarse or fine aggregate for better strength performance of the concrete. Table 1 and Table 2 [65][66][67][68][69][70][71][72][73][74] were generated by summing up collected data from the existing literature review showing the replacement of fine, coarse, and combined aggregate with crumb rubber in SCC [39] and RCC. Most researchers agree that replacing the rubber with fine aggregate in the case of SCC would be more beneficial than the coarse or total aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers [54,60,61] concluded that the total aggregate replacement with crumb rubber would perform better by lowering the strength reduction that occurs when adding crumb rubber to the concrete mix, as in the case of fine or coarse aggregate replacement. Similarly, in RCC, most of the researchers [65][66][67][68][69][70][71][72][73][74] studied the replacement of fine aggregate or combined (total aggregate). Most investigations have explored the utilization of crumb rubber as fine aggregate replacement.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]. In addition, various admixtures modified both fresh and hardeening properties of concrete which include crumb rubber (CR) [4,5] nanomaterials [6][7][8][9], polymer materials [10][11][12], fiber-reinforcement [13][14][15][16][17], and pozzolonic materials [18][19][20].…”
Section: Introductionmentioning
confidence: 99%